2020
DOI: 10.1089/cren.2020.0027
|View full text |Cite
|
Sign up to set email alerts
|

Trapped Flexible Ureteroscope in Ureteral Access Sheath During Retrograde Intrarenal Surgery: An Unexpected Problem

Abstract: Background: Instrument-related complications occur occasionally with the use of flexible ureteroscopes. In this study, we present a unique problem related to instrument malfunction of flexible ureteroscope during retrograde intrarenal surgery. Case Presentation: A 60-year-old male patient with a 1.2 cm left upper ureteral stone initially underwent semirigid ureteroscopic laser lithotripsy and during the procedure the stone got retropulsed into middle calix of the kidney. Subsequently, a 9.5F (internal diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The flexible ureteroscope may be stuck in the urinary system during FURS. Urologists need to be aware of it and take action in time, [14][15][16] or severe complications will be caused. Moreover, the flexible shaft is inside the patient's urinary system, and the urologist can only see the endoscopic view in front of the scope.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The flexible ureteroscope may be stuck in the urinary system during FURS. Urologists need to be aware of it and take action in time, [14][15][16] or severe complications will be caused. Moreover, the flexible shaft is inside the patient's urinary system, and the urologist can only see the endoscopic view in front of the scope.…”
Section: Discussionmentioning
confidence: 99%
“…As stated in the introduction section, three interactive forces exist between the flexible ureteroscope and the environment during manipulation, including axial force, axial torque, and bending knob's torque. If the flexible ureteroscope is trapped in the urinary tract for unexpected reasons, 14–16 the axial force and torque will help urologists to notice this dangerous event and avoid worse complications. The torque exerted on the flexible ureteroscope's bending knob is also important, which helps protect the flexible ureteroscope because excessive torque will damage it 18 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a recent publication showed that UAS increased the odds of a post-operative emergency department visit and re-hospitalization, without better SFR ( 18 ). Unusual but dramatic complications related to the UAS have been described, such as the entrapment of a flexible ureteroscope (fURS) inside the sheath due to a breakage of the outer surface of the scope caused by excessive manipulation ( 20 ).…”
Section: Commentmentioning
confidence: 99%